Dioxin-like biological activity of organic extracts from sediments and fish livers sampled along the Israeli Mediterranean and Red Sea coasts. Issue 1 (15th September 2015) - Yudkovski, Yana; Herut, Barak; Shefer, Edna; Tom, Moshe
Highlights: The CALUX bioassay was used to determine TEQ values of DLCs in fish and sediments. Baseline levels of DLCs along the coasts of Israel were determined. Dioxin-like compounds are potential coastal pollutants only inside Israeli anchorages. HRGC/HRMS profiles of the composing compounds of selected samples were provided. Abstract: This study provides, for the first time, a baseline evaluation of dioxin-like biological activity in sediments and fish sampled in- and adjacent to anchorages along the Mediterranean and Red Sea coasts of Israel. It indicates the effect of past pollution, still present in the sediments of older Israeli harbors, with putative contribution of still existing sources of pollution. A commercial reporter gene bioassay was used to evaluate the biological activity of dioxin-like compounds extracted from the samples. HRGC/HRMS analysis of several samples contributed a profile of dioxin-like compounds in sediments and fish. The results point out 1, 2, 3, 4, 6, 7, 8-HeptaCDD, 2, 3, 4, 6, 7, 8-HexaCDF, 1, 2, 3, 4, 6, 7, 8-HeptaCDF, РСВ-126 and РСВ-118 as major contributors to the dioxin-like activity in sediments. It indicates polychlorinated biphenyls non-selective absorption in fish livers, in contrary to a biased accumulation of poorly chlorinated and more potent dibenzodioxins and dibenzofurans.